The Effect of Organizational Climate on Sell‐side Analyst Turnover and Performance. - Chua, Wai Fong; Kuang, Yu Flora; Wu, Yi (Abacus, 2024)
This paper investigates whether and how organizational climate (OC) in brokerage firms affects analyst turnover and performance. We find that firms with a lower‐rated OC have a higher likelihood of analyst turnover. Also, when analysts leave and switch brokerage firms, they are more likely to move to a firm with a higher‐rated OC and will deliver more accurate forecasts after switching firms. However, the performance improvements in better‐rated OC firms are significant only for the initial years of the analysts' employment in the new firms. We also show that OC‐related analyst turnover negatively affects the performance of incumbent analysts, especially for those non‐All‐Star incumbent analysts, while these adverse performance effects are also transitory and last for two years only. Thus, our findings indicate that OC only has a short‐lived effect on the behaviour of both leaving and remaining analysts, which challenges the long‐held assumption that investments in a positive OC will always be associated with lower employee turnover and higher individual performance. We explain our results as arising from the high levels of labour mobility within the brokerage industry and the transparency of analyst forecasts as a public performance measure.